Active learning and knowledge in physics: a reading from classroom work (2021)
This research article shows the findings of a study that sought to demonstrate the results of a methodological intervention implemented in classes of an eleventh-grade course in the area of Physics, in a public school in the city of San José de Cúcuta, Colombia. The intervention consisted of applying some active learning strategies accompanied by methodological tools such as collaborative work in order to measure the impact of the intervention on the level of disciplinary knowledge of students with a pre-test and post-test. The results show a significant increase with a value of 0.49 at the end of the intervention, which suggests that the subjects participating in the study improved their level of conceptual appropriation in physics after the application of active learning strategies.